Imagining money - ALLEN, J.G. (Institutional Knowledge at Singapore Management University, 2020)
John Clarke presents the theme of this volume by asking why we might speak of “imagined economies”. It is, he answers, “to interrupt the apparent ubiquity of economies”, to provide a moment for “a pause for thought”. In this chapter, I explore the role that imagination plays in the creation and maintenance of a money system. Money is important to the existence and functioning of an economy.1 Money, too, seems ubiquitous and naturally-occurring, so I want to pause and consider why it is that we might have money and what exactly it is doing. Different objects have served as money, or tokens of money, in different societies.